2018
DOI: 10.3390/ijerph15122734
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Burial and Response to Climate Change and Anthropogenic Disturbance in Chaohu Lake, China

Abstract: Lakes are a crucial component of the global carbon and nitrogen cycle. As a trend of enhanced human activities and climate change, the mechanisms of burial remain poorly understood. In this study, diverse biogeochemical techniques were applied to analyze the temporal variation of organic carbon and nitrogen burial rates in Chaohu Lake. The results showed that burial rates have ranged from 9.39 to 35.87 g C m−2 yr−1 for carbon and from 1.66 to 5.67 g N m−2 yr−1 for nitrogen since the 1860s. The average rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…As an important component of the reservoir water environment, sediments have the contradictory characteristics of “source–sink” for pollutants. During the long operation period of a reservoir, sediments have been receivers of various pollutants including point and nonpoint sources [1,2]. With the perennial accumulation of pollutants and mineralization of sedimentary organic matter, concentrations of a variety of constituents in sediments are many times greater than those in water.…”
Section: Introductionmentioning
confidence: 99%
“…As an important component of the reservoir water environment, sediments have the contradictory characteristics of “source–sink” for pollutants. During the long operation period of a reservoir, sediments have been receivers of various pollutants including point and nonpoint sources [1,2]. With the perennial accumulation of pollutants and mineralization of sedimentary organic matter, concentrations of a variety of constituents in sediments are many times greater than those in water.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that only approximately 20% of pollutants are discharged via Dianchi Lake processes while the rest remain in the sediment, allowing them to be easily released into the overlying water again (He et al, 2015). This phenomenon is one of the reasons for the higher ON content (294-6140 mg kg − 1 ) in Dianchi Lake sediment than in other eutrophic lake sediments, such as Chaohu Lake (195-1076 mg kg − 1 ) and Taihu Lake (278-4687 mg kg − Loading [MathJax]/jax/output/CommonHTML/fonts/TeX/fontdata.js 1 ) (Yu et al, 2018;Wu et al, 2019). In addition, the speci c conditions of the sediment core sampling region affect ON burial.…”
Section: In Uencing Factors On the Organic Nitrogen Burialmentioning
confidence: 99%
“…It accumulates in the sediment and is easily converted to nitrate and ammonia via mineralization. Most of the converted ammonium and nitrate are released into the overlying water, which may cause algal blooms (Galman et al, 2008;Yu et al, 2018). The effects of algal residues, which are considered important autochthonous sources, on organic matter burial have been widely studied (Anderson et al, 2014;Leithold et al, 2016).…”
Section: Introductionmentioning
confidence: 99%